King of Scents - Agarwood - Saiful Nizam, Tajuddin; Kanwal, Deep (2019)
Agarwood is the resinous wood of a tree from Aquilaria and Gyrinops species, which is highly prized as a premium raw material used in fragrances and traditional medicines. The trees naturally grow in the forests of Southeast Asia (SEA), primarily distributed in countries namely India, Malaysia, Bhutan, Thailand, Vietnam, Cambodia and Sri Lanka. The history of agarwood stretches back to ancient times and its use has largely been associated with regional, cultural and religious beliefs. Agarwood is also considered as sacred. Due to its extremely high value, the species has been hunted down from its natural habitat in the forests, reducing its availability at an alarming rate. The two species are now considered endangered and have been listed in Appendix II of the Convention on International Trade of Endangered Species (CITES) of Wild Fauna and Flora. Enforcement of CITES on agarwood put the activities of exporting and importing agarwood from the wild under very stringent control.